Author Correction: Subwavelength angle-sensing photodetectors inspired by directional hearing in small animals. Issue 12 (December 2018) - Yi, Soongyu; Zhou, Ming; Yu, Zongfu; Fan, Pengyu; Behdad, Nader; Lin, Dianmin; Wang, Ken; Fan, Shanhui; Brongersma, Mark
In the version of this Letter originally published, Zongfu Yu was mistakenly not noted as being a corresponding author; this has now been corrected in all versions of the Letter.